2014
DOI: 10.1002/aqc.2473
|View full text |Cite
|
Sign up to set email alerts
|

Habitat suitability, coverage by protected areas and population connectivity for the Siamese crocodile Crocodylus siamensis Schneider, 1801

Abstract: With estimates of fewer than 1000 mature individuals in the wild, the critically endangered Siamese crocodile, Crocodylus siamensis Schneider, 1801, is one of the least known and at the same time most threatened crocodilian species in the world. Populations have already been depleted to approximately 20% of their former size with habitat destruction, alterations, and loss being the main drivers of population declines. Habitat suitability models were computed using a combination of bioclimatic and remote sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Values were extracted from the seven predictor variables for each of the 46 species. Pearson correlations were calculated for all pairs of variables for all species (Hodd et al, 2014;Ihlow et al, 2014). Bio 18 and Bio 19 were removed for all species in Biomod because they were highly correlated with many of the other predictors.…”
Section: Pseudo-absence Creationmentioning
confidence: 99%
“…Values were extracted from the seven predictor variables for each of the 46 species. Pearson correlations were calculated for all pairs of variables for all species (Hodd et al, 2014;Ihlow et al, 2014). Bio 18 and Bio 19 were removed for all species in Biomod because they were highly correlated with many of the other predictors.…”
Section: Pseudo-absence Creationmentioning
confidence: 99%
“…C. siamensis feeds on a diverse variety of prey, including invertebrates, frogs, reptiles, birds, and mammals 8,9 . Nonetheless, the crocodiles are now critically endangered due to habitat loss, with a large proportion of them held in commercial farms in Southeast Asian countries, such as Thailand 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Although C. siamensis is still considered one of the least understood crocodilians, 10,11 the therapeutic potentials of crocodiles have attracted increased attention in recent years. The proposition that crocodiles may have developed strong immune systems began from the ecological observation that crocodiles are able to tolerate high exposures to heavy metals, radiation, and pathogenic micro‐organisms in their habitats 12‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the results of studies on the ecology of C. siamensis have begun to be widely publicized although this crocodile is less widely known. Ihlow et al (2014) reported that the number of C. siamensis was estimated to the global population be less than 1,000 adult individuals in the wild. Crocodile skin trading activities and the search for crocodile tillers to be farmed in the mid and the late 20th century were considered as the main cause of its population decline.…”
Section: Introductionmentioning
confidence: 99%